NUMERICAL SIMULATION OF IN-CYLINDER HEAT TRANSFER LOSSES FROM DIESEL ENGINE - ALIAS, MOHAMMAD IZZAT (IRC, 2018)
First and foremost, I would like to express my greatest appreciation and gratitude to Allah S.W.T., for showering me with guidance, strength, and wisdom that had helped me in completing this project. I would also like to express my utmost gratitude to my supervisor Dr. Mior bin Azman Meor Said for aiding me through the whole project with great support and encouragement. Furthermore, my deepest appreciation goes to Mr. Firmansyah, and from Centre for Automotive Research and Electrical Mobility (CAREM) and my lecturer, IR Dr Masri Bin Baharom for sharing their technical knowledge and assisting me throughout accomplishing this project. Next, I would like to express my deepest gratitude to both my parents for their continuous encouragement and support throughout the duration of this project. I would also like to express gratitude to both my external examiner, Dr Jundika Candra Kurnia and AP Dr Ahmad Majdi Bin Abdul Rani, for their very insightful guidance on my project and how it can be improved further. Last but not least, I would like to give my gratitude to my colleagues in Mechanical Engineering for their assistance in this project.